Respuestas

2013-02-13T01:34:04+01:00

a) 3x-4y=41
11x+6y=47

de la primera despejas x o y ahora vamos a despejar x
x=(41+4y)/3
reemplezamos abajo
11((41+4y)/3)+6y=47
(62y/3)+(451/3)=47
y=--5
reemplazas donde despejaste x para ontener su valor
x=(41+4y)/3=61/3

b) 10x-3y=36
2x+5y=-4
x=(3(y+12))/10

2((3(y+12))/10)+5y=-4
(3(y+12))/5)+5y=-4
(28y)/5 + (36/5) = -4
y=-2
x=(3(-2+12))/10=3

c) 18x+5y=-11
12x+11y=31

y=-(18x+11)/5
12x-11((18x+11)/5)=31
x=-2

y=-(18*-2+11)/5=5

d) 12x-14y=20
12y-14x=-19

x=(7y+10)/6

12y-14((7y+10)/6)=-19
y=-1

x=(7y+10)/6=(1/2)

e) 9x+11y=-14
6x-5y=-34

x=-(11y+14)/9

6(-(11y+14)/9)-5y=-34
y=2

x=-(11y+14)/9=-4

f) 11x-9y=2
13x-15y=-2

x=(9y+2)/11

13((9y+2)/11)-15y=-2
y=1

x=(9*1+2)/11=1

g) 9x+7y=-4
11x-13y=-48

x=-(7y+4)/9
11(-(7y+4)/9)-13y=-48
Y=2

x=-(7*2+4)/9=-2

h) 15x-y=40
19x+8y=236

x=(y+40)/15
19((y+40)/15)+8y=236
y=20

x=(20+40)/15=4